Auditoria interna como instrumento de governança pública na dimensão controle: estudo nas universidades federais brasileiras - Moreira, Lúcia Helena (2015)
Public governance is related to the government's ability to meet social demands on public services, through transparent action and accountability of agents and public managers for their actions. The fundamental principles of governance can be observed in public entities, and reflected, according to the study 13 of the IFAC, in four dimensions: behavioral patterns; organizational structures and procedures; control and external report. The focus of this study are the dimensions control and external report, specifically on topics related to internal audit and external control, within the Brazilian federal-government universities. The main purpose of the research was based on analyzing the influence the adoption of good practices of public governance by internal audits of the Brazilian federal-government universities on the regularity of checks and balances of these institutions, adopting methodology, which is characterized as descriptive and exploratory method, based on procedures for bibliographic and documentary research. It is a qualitative approach, guided by the judgments of the sample of Union's Court of Auditors on the checks and balances of the federal universities members content analysis, in addition to data collection by questionnaire. The survey sample consists of federal universities whose internal audit units are older, if opting for a longitudinal section that covers internal audits created by the year 2001. It was found a partial adoption of practices related to internal audit, recommended by the IFAC, for almost all the surveyed federal universities, except the Minas Gerais (UFMG), which fully met the recommendations. Content analysis of TCU rules pointed to major non-conformities in the areas of Personnel Management, Procurement and Accounting. The study concluded that there is not a relationship of influence between the level of adherence to good public governance practices and the regularity of checks and balances of these institutions, as indicated in the results of 11 out the 13 federal universities analyzed.